Rosiglitazone Induced Smooth Muscle Relaxation and Reversal Via L-Bisphenol A Diglycidyl Ether - Jahan, Sarwat (International Journal of Pathology, 2023)
Background: PPAR-γ (Peroxisome Proliferator Activated receptor gamma) ligands are capable of suppressing the expression of a variety of genes involved in inflammation present in the macrophages upon activation and carry the potential of being the anti-inflammatory targets for diseases of airways. Agonists of PPAR-γ including thiazolidinediones can, therefore be utilized as a potential treatment for inflammatory diseases of the airways such as asthma and COPD (chronic obstructive pulmonary disease).Objective: To establish the bronchodilatory effect of RosiglitazoneMethodology: The study was performed using the isolated pieces of smooth muscle of the trachea of total 20 guinea pigs divided into four groups. Contractions were noted via an oscillograph having four channels with the help of a displacement transducer. Effects of Rosiglitazone on the smooth muscles of the trachea were noted through adding histamine and then blocking the PPAR receptors via addition of BADGE (L-Bisphenol A Diglycidyl Ether).Results: The group given histamine showed the mean ± standard error of mean of the contractions varying from 10 to 83 mm. A decrease in the histamine induced contractions was noted on addition of Rosiglitazone. BADGE enhanced the histamine induced contractions and reduced the effect of rosiglitazone on histamine induced contractions. The obtained values were utilized for plotting curves of semi log and were compared among different groups.Conclusion: The results solidify the hypothesis that thiazolidinediones produce the relaxation of the smooth muscles via activation of PPAR gamma receptor.